Preparation of nanoparticle-stabilized foam fracturing fluid and its foam stabilization mechanism - YANG Zhaozhong, ZHENG Nanxin, ZHU Jingyi, LI Xiaogang (Youqicang pingjia yu kaifa)
The synergistic effect of SiO2 nanoparticles （SNP） and surfactants can provide a new idea for the preparation of foam fracturing fluid suiTable for harsh formation conditions. In order to prove it, the synergistic foam stabilization ability of SNP and five types of surfactants is evaluated, and the optimal foams system is selected based on the foams comprehensive value. The proppant carrying ability, rheology, and stability of the selected foam fracturing fluid system are evaluated, and the performance improvement of the fracturing fluid by SNP is analyzed. At the same time, the optical microscope observation and SEM experiment are used to reveal the foam stabilization mechanism of SNP. The system screening experiments show that the synergistic effect of TTAB and SNP is the most obvious. The comprehensive foam value reaches 15 288 mm·s, and the half-time of water drainage increases by 145 %. The performance evaluation experiments show that SNP can improve the elastic modulus of the interfacial liquid film, improve the proppant supporting capacity of the liquid film, reduce the settling velocity of proppant which help foam fracturing fluid bring proppants into deeper fractures. SNP can also improve the surface roughness of liquid film and thus enhance the shear resistance of foam fracturing fluid. Adding proppants to the system can weaken the stability of foam. The weakening effect of ceramsite is stronger than that of quartz sand, and the weakening effect of high mesh size is stronger than that of low mesh size. The stabilization mechanism study is revealed by the SNP aggregation at Plateau is observed in the foam microstructure which can block the drainage channels. Moreover, SNP could prevent the coarsening and drainage of foam. By the macroscopic observation, SNP-stabilized bubbles are more stable in term of more bubble number, smaller bubble size and more uniform bubble size distribution.